نسبة انتشار الداء السكري وماقبل السكري عند مرضى التهاب محفظة الكتف (خبرة مشفيي الأسد وتشرين الجامعيين في اللاذقية بين عاميي 2015-2016) - حسن عبد الرزاق; الدو كاسر; الخوري راما (Latakia University Journal -Medical Sciences Series, 2018)
Adhesive capsulitis has been used to describe a painful and stiff shoulder. Adhesive capsulitis is most commonly classified as either primary or secondary. Adhesive capsulitis has been described as having three sequential phases: a painful stage, a freezing stage, and a thawing or recovery stage. The estimated prevalence is 11–30% in diabetic patients and 2–10% in nondiabetics. The research aims to knowledge the prevalence of a Diabetic Condition (diabetes mellitus and prediabetes) and Adhesive Capsulitis of the Shoulder. This was a prospective study conducted in Al-Asad and Tishreen academic hospitals in Lattakia city, Syria, ovar a period of one year. A total of 100 patients with the diagnosis of adhesive capsulitis. All patients underwent a detailed medical history and full examination of the shoulder joint followed by blood sugar in the morning and a simple radial image of the shoulder Patients were divided into 63 females and 37 male. The ages ranged between 40-70 years old. Number of patients with diabetes was 45 in the rate of 45%, patients with prediabetes was 19 in the rate of 19%, and non diabetes was 36 in the rate of 36%. التهاب محفظة الكتف مرض مجهول السبب مع وجود صفتين رئيسيتين له: الألم والانكماش. يصنف إلى بدئي وثانوي. يمر التهاب محفظة الكتف عادةً بثلاث مراحل واضحة ومتميزة هي: مرحلة الألم والتحدد النسبي في الحركة, مرحلة الالتصاق, ومرحلة الانحلال. حيث بينت الدراسات انتشار التهاب المحفظة لدى السكريين بنسبة 30% بينما بلغت النسبة 2-10% عند غير السكريين. فهدف دراستنا هو معرفة نسبة النتشار الداء السكري وماقبل السكري عند المرضى المراجعين لمشفيي الأسد وتشرين الجامعيين والذين لديهم احدى مراحل التهاب محفظة الكتف. الطرائق والمواد: دراسة مستقبلية أجريت في مشفيي الأسد وتشرين الجامعيين في مدينة اللاذقية خلال عام واحد, شملت 100 مريض التهاب محفظة كتف. حيث تم أخذ قصة سريرية مفصلة وإجراء فحص سريري دقيق للكتف مع اجراء سكر دم صباحي وصورة شعاعية بسيطة للكتف. النتائج: كان عدد الإناث (63) والذكور (37).. وتراوحت الأعمار بين 40-70 سنة.. عدد المرضى المصابين بالسكري (45) مريض, المصابين بماقبل السكري (19) مريض, بينما غير السكريين (36) مريض.